Labeling playboy novel Hello Cello perspective: field psychology Kurt Lewin - Novalisty, Rediva (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to describe labeling playboy novel “Hello Cello” perspective: field psychology Kurt Lewin. The approach used in this study is literary psychology which uses qualitative-descriptive because it uses data in the form of descriptive-causality exposure. Kurt Lewin's social psychology study, which explains the concept of field, explains that if we want to know a person's psychology, we must also research or at least know the environmental conditions around which a person lives. In the novel, Cello is depicted who lives in an environment that always gives a bad view or  negative stereotypes to him. They assume that Cello is a playboy. Everything he does is not based on sincerity, but just a tactic to  attract the attention of the women he wants to approach. In addition to influencing psychology, the influence of living space  or field gives inner conflict or feelings to the characters. Inner conflict influences the emergence of thoughts on self-attitude.